2013
DOI: 10.1158/1541-7786.mcr-13-0096
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Metastasis Suppressor-1 Promoter Methylation in Primary Breast Tumors and Corresponding Circulating Tumor Cells

Abstract: Breast Cancer Metastasis Suppressor-1 differentially regulates expression of multiple genes, leading to metastasis suppression without affecting orthotopic tumor growth. We evaluated BRMS1 promoter methylation as prognostic biomarker in primary breast tumors and studied BRMS1 promoter methylation in a subset of corresponding Circulating Tumor Cells (CTC) for the first time. We analyzed 118 formalin-fixed paraffin embedded samples: 5 pairs of breast tumors and adjacent non-cancerous tissues, 14 non-cancerous ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 36 publications
1
49
1
Order By: Relevance
“…Chimonidou et al analyzed CTCs and cell‐free DNA in breast cancer for methylation of a tumor suppressor gene SOX17 promoter . In another study of breast cancer, methylation of a metastasis suppressor gene was studied in primary tumor and CTCs, and the authors investigated its effect on survival . Whilst the rarity of CTCs offers challenges in enrichment and downstream assay feasibilities, cell free DNA suffer from similar limitations with respect to available amounts .…”
Section: The Futurementioning
confidence: 99%
“…Chimonidou et al analyzed CTCs and cell‐free DNA in breast cancer for methylation of a tumor suppressor gene SOX17 promoter . In another study of breast cancer, methylation of a metastasis suppressor gene was studied in primary tumor and CTCs, and the authors investigated its effect on survival . Whilst the rarity of CTCs offers challenges in enrichment and downstream assay feasibilities, cell free DNA suffer from similar limitations with respect to available amounts .…”
Section: The Futurementioning
confidence: 99%
“…In CTCs of patients with operable breast cancer, promoter methylation of BRMS1 was observed in 32.1%, while in CTCs of patients with verified metastasis, promoter methylation of BRMS1 was observed in 44.4% (Obermayr et al., 2013). BRMS1 promoter was found to be highly methylated in CTC, while immunofluorescence studies in the same cytospins have shown that it was down regulated at the protein level in CTC as well (Chimonidou et al., 2013b). Moreover, we have recently shown that methylation of BRMS1 promoter in circulating tumor DNA isolated from plasma of NSCLC patients provides important prognostic information and merits to be further evaluated as a circulating tumor biomarker (Balgkouranidou et al., 2014).…”
Section: Dna Methylation Analyses Of Ctcsmentioning
confidence: 99%
“…The specificity and sensitivity of the MSP assay for BRMS1 promoter methylation has been previously verified (Chimonidou et al , 2011, 2013). …”
Section: Methodsmentioning
confidence: 85%
“…The methylation status of BRMS1 gene in tissue samples was detected by conventional MSP by using specific primer pairs for both the methylated and unmethylated promoter sequences as previously described (Chimonidou et al , 2013). Each MSP reaction was performed in a total volume of 25  μ l. In all, 1  μ l of SB-converted DNA was added into a 24  μ l reaction mixture that contained 0.1  μ l of Taq DNA polymerase (5 U  μ l −1 , hot start GoTaq Polymerase; Promega, Madison, WI, USA), 5  μ l of the supplied 10 × PCR buffer, 2.0  μ l of MgCl 2 (50 mmol l −1 ), 0.5  μ l of dNTP's (10 mmol l −1 ; Fermentas, Carlsbad, CA, USA) and 1  μ l of the corresponding forward and reverse primers (10  μ mol l −1 ); dH 2 O was added to a final volume of 25  μ l. Sodium bisulfite-treated DNA was amplified in two separate MSP reactions, one with a set of primers specific for the methylated and one for the unmethylated BRMS1 promoter sequences.…”
Section: Methodsmentioning
confidence: 99%